Changing Patterns of Politics in Africa - Adebayo Olukoshi (Cadernos de Estudos Africanos)
In an attempt at lining out a framework for the debate on pattern changes in African politics, this articles focuses mainly on the structures of interaction on the «national» level. In this perspective, it points out a series of processes common to all of Africa which have been provoking alterations in the original patterns. It lists a number of problem areas important for future research, but does not propose hypotheses for future patterns. This part is complemented by a critical discussion of the attempts at interpreting the political processes in Africa which have to date been made in the social sciences, denouncing their sometimes flagrant inadequacies.